Adversity and persecutory ideation: A moderated mediational model. (December 2017) - Valiente, Carmen; Espinosa, Regina; Villavicencio, Patricia; Cantero, Dolores; Fuentenebro, Filiberto
Abstract: Adversity has been identified as an important factor in models of psychopathology and can help in understanding persecutory ideation, although potential moderators and mediators for adult psychopathology have not been sufficiently examined. Experiential avoidance (EA) and Self-esteem (SE) are relevant factors to understand how adversity leads to persecutory ideation. This study hypothesized that adversity would be associated with persecutory ideation through heightened EA, and that this association would be strengthened in individuals with a discrepant high SE. Participants with persecutory ideation (n = 52), with depression (n = 35) and healthy controls (n = 51) were assessed with the Trauma History Screen, the Paranoia and Deservedness Scale, and the Beck Depression Inventory. A SE discrepancy index was calculated subtracting the normalized explicit SE score from the normalized implicit SE score (measured by a version of a Go/No-go association task). Our analysis revealed that adversity was associated with higher levels of paranoia and was mediated by EA. In addition, we found that the relationship between adversity and EA was moderated by SE discrepancy. Identification of moderating and mediating variables allows for increased understanding of persecutory ideation and the processes that should be targeted in the course of recovery. Highlights: Adversity has been identified as an important factor in models of psychosis. Moderators and mediators may provide a better understanding of persecutory ideation. Experiential avoidance mediated the relationship between adversity and paranoia. Adversity and experiential avoidance was moderated by self-esteem discrepancy. Improving the self for people with persecutory ideation is crucial.